Effects of Prior Intensive Insulin Therapy on Cardiac Autonomic Nervous System Function in Type 1 Diabetes Mellitus: The Diabetes Control and Complications Trial/Epidemiology of Diabetes Interventions and Complications Study (DCCT/EDIC) - Pop-Busui, Rodica; Low, Phillip A.; Waberski, Barbara H.; Martin, Catherine L.; Albers, James W.; Feldman, Eva L.; Sommer, Catherine; Cleary, Patricia A.; Lachin, John M.; Herman, William H. (Circulation (New York, N.Y.), 2009)
Background— The Epidemiology of Diabetes Interventions and Complications (EDIC) study, a prospective observational follow-up of the Diabetes Control and Complications Trial (DCCT) cohort, reported persistent benefit of prior intensive therapy on retinopathy and nephropathy in type 1 diabetes mellitus. We evaluated the effects of prior intensive insulin therapy on the prevalence and incidence of cardiac autonomic neuropathy (CAN) in former DCCT intensive and conventional therapy subjects 13 to 14 years after DCCT closeout. Methods and Results— DCCT autonomic measures (R-R variation with paced breathing, Valsalva ratio, postural blood pressure changes, and autonomic symptoms) were repeated in 1226 EDIC subjects in EDIC year 13/14. Logistic regression models were used to calculate the odds of incident CAN by DCCT treatment group after adjustment for DCCT baseline covariates, duration in the DCCT, and quantitative autonomic measures at DCCT closeout. In EDIC year 13/14, the prevalence of CAN using the DCCT composite definition was significantly lower in the former intensive group versus the former conventional group (28.9% versus 35.2%; P =0.018). Adjusted R-R variation was significantly greater in the former DCCT intensive versus the former conventional group (29.9 versus 25.9; P <0.001). Prior DCCT intensive therapy reduced the risks of incident CAN by 31% (odds ratio, 0.69; 95% confidence interval, 0.51 to 0.93) and of incident abnormal R-R variation by 30% (odds ratio, 0.70; 95% confidence interval, 0.51 to 0.96) in EDIC year 13/14. Conclusions— Although CAN prevalence increased in both groups, the incidence was significantly lower in the former intensive group compared with the former conventional group. The benefits of former intensive therapy extend to measures of CAN up to 14 years after DCCT closeout.